Chapter Umanità e cecità: nascondigli identitari tra José Saramago e José Ortega y Gasset - Antony, Jean Paul d’ (Firenze University Press, 2023)
The text discusses the unfolding of identities, especially in European society, in dialogue with the analysis of Saramago’s blindness and the idea of mass-man in Ortega y Gasset. The objective is to rethink the transits and unraveling of humanization processes that transcend the European Union project and the speeches of David Maria Sassoli, as president of the European Parliament.